Management of the Medically Compromised Cases in Orthodontic Practice - Gowri Sankar Singaraju (Asian Journal of Medical Sciences, 2011)
Orthodontic therapy is no longer restricted only for healthy patients. With the better management of serious medical problems and increased quality of life expectations, medically compromised individuals are now regular visitors to the orthodontic clinics in every part of the world. As such, there is no absolute contraindication of orthodontic treatment in most of these conditions. A slight modification of the normal orthodontic treatment protocol is obligatory in such patients according to their medical condition. This article reviews and suggests the orthodontic treatment protocol for some common medical conditions.